Beam Steering: Structured Optical Materials Controlled by Light (Advanced Optical Materials 15/2018). Issue 15 (6th August 2018) - Nocentini, Sara; Martella, Daniele; Parmeggiani, Camilla; Zanotto, Simone; Wiersma, Diederik S.
Abstract : A micro‐structured beam steering device controlled by light was demonstrated by Sara Nocentini and co‐workers (article number1800167 ). The research reports how to exploit light itself to tune and switch photonic materials and components. Specifically, the auhors controlled the deformation of a periodic shape‐changing liquid crystalline polymeric structure, therefore tuning the diffracted beam directions. The cover image is a photograph of the diffraction profile.